Decline in hepatitis E virus antibody prevalence in southeastern Germany, 1996‐2011. Issue 4 (28th August 2014) - Wenzel, Jürgen J.; Sichler, Mathias; Schemmerer, Mathias; Behrens, Gundula; Leitzmann, Michael F.; Jilg, Wolfgang
<x xml:space="preserve">Abstract</x> In the past decade, an increasing frequency of acute hepatitis E was noted in Germany and other European countries. Moreover, a high prevalence (17%) of hepatitis E virus (HEV) immunoglobulin G antibodies (anti‐HEV) was recently found in the adult German population. Although this suggests an emerging pathogen, reports from other countries gave hints to a completely new aspect: a possible decrease in anti‐HEV prevalence during the last decades. To investigate the time trends of hepatitis E in southeastern Germany, we performed anti‐HEV testing in sera taken from adults in 1996 and 2011. Surplus serum specimens stored during routine operations of our diagnostic laboratory were used. The sample comprised two sets of 1, 092 sera taken in 1996 and 2011, each with 182 specimens in six age groups from 20‐79 years. Testing was performed using an HEV IgG enzyme immunoassay (EIA, Axiom Diagnostics), and the recomLine HEV IgG immunoblot (Mikrogen). A significant difference in anti‐HEV prevalence was observed between the two groups: 50.7% of individuals tested positive in the 1996 group as compared to 34.3% in 2011 (EIA, P < 0.001). Results by immunoblot analysis were 20.5% (1996) versus 14.5% (2011), P < 0.001. Differences were found in all age groups and were more pronounced for the 20‐39‐year age group. Conclusion: The prevalence of anti‐HEV has decreased significantly in the past decades in southeastern Germany. The phenomenon of HEV being an emerging pathogen is thus most probably due to an increasing awareness of the disease. (Hepatology 2014;60:1180–1186)